Peran Komunikasi Pada Orang Tua Tipe Keluarga Pluralistik dalam Pendidikan Seksual Mahasiswa Rantau Telkom University - Putri, Shafira Angelita Setiya; Ramadhana, Maulana Rezi; Priastuty, Chairunnisa Widya (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The movement of overseas students to their university's city often leads to cultural clashes and adaptation challenges. Open communication within families, akin to the pluralistic family model, is crucial amid these challenges. Cultural clashes, exemplified by sexual issues on Telkom University's campus, underscore the parental role in providing positive sexual education to enhance students' awareness. This study aims to explore how parental communication, particularly in pluralistic families, influences overseas students' sexual education and awareness. Using qualitative methods, including in-depth interviews and observations, the research reveals the significant impact of parental communication on sexual education at Telkom University. Pluralistic families employ open communication, acting as friends to facilitate effective advice reception. Parental messages greatly influence students' attitudes toward sexual education.